أثر المتغيرات الديموغرافية الصناعية على القطاعات الاقتصادية في سورية - حيدر عز الدين; يوسف حسين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى دراسة العلاقة بين المتغيرات الديموغرافية الصناعية حيث يعتبر قطاع الصناعة من أهم القطاعات الاقتصادية السورية وأكثرها تشغيلا للعمالة, وبين مدخلات هذا القطاع بشكل خاص و مدخلات باقي القطاعات الاقتصادية. تم التوصل إلى عدة نتائج أهمها وجود أثر ذات دلالة إحصائية بين مدخلات القطاع الصناعي وعدد العاملين الكلي في قطاع الصناعة, ووجود علاقة بين هذه المدخلات وبين التركيب النوعي والقطاعي والتعليمي للعاملين في القطاع الصناعي, كما توصل البحث إلى وجود تأثير ذو دلالة إحصائية للمتغيرات الديموغرافية على مدخلات باقي القطاعات الاقتصادية مجتمعة من خلال المعادلة الارتباطية القانونية التالية: This research aims at studying the relationship between the industrial demographic variables as it is one of the most important Syrian economic sectors and the most labor- employment, and the inputs of this sector in particular and the inputs of the rest of the economic sectors. A number of results were found, most notably the existence of a statistically significant relationship between the inputs of the industrial sector and the total number of workers in the industrial sector, and the relationship between these inputs and the qualitative, sectoral and educational structure of the industrial sector. The research also found a statistically significant effect of the demographic variables on inputs The rest of the economic sectors combined through the following canonical correlation: